Keperluan perkhidmatan kaunseling di Perbadanan Pembangunan Ekonomi Sarawak - Dayang Hasma Nissa, Awang Yusof. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The main purpose of this research is to analyze the needs of counseling service in Sarawak Economic Development Corporation (SEDC). This research is to foresee the worker's perception towards the need of counseling, to see the perception of the employee towards counselor and counseling service. Besides, this research is to analyze the issues arises and the need itself of counseling service in an organization. The sample for this research is for 41 respondent and the data that has been collected will be analyzed using SPSS version 11.0. This research will be using descriptive and frequency method in analyzing the data. Through the analysis that has been done, it has shown that the employees in SEDC really need the counseling service not only to help them to overcome their problems at the workplace but also the service is able to help the employees and employers to increase the organization's productivity and help them to develop their skill and knowledge. As a conclusion, this research has been done to know that all variables has link to the needs of counseling service in the organization. Thus, it is hoped that the organization will look into this matter for the interest of everyone. Besides, it also hoped that this research will be used for future researcher as a main reference.